2017
DOI: 10.1007/s11914-017-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Mechanobiology

Abstract: Purpose of this Review Over the past decades, osteocytes have emerged as mechano-sensors of bone and master regulators of bone homeostasis. This article summarizes latest research and progress made in understanding osteocyte mechanobiology and critically reviews tools currently available to study these cells. Recent Findings Whereas increased mechanical forces promote bone formation, decrease loading is always associated with bone loss and skeletal fragility. Recent studies identified cilia, integrins, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 63 publications
1
138
0
2
Order By: Relevance
“…OCs are key regulators of the bone modeling process, and several studies have shown that CD4 + T cells are closely related to the differentiation of OCs by secreting RANKL (Uda, Azab, Sun, Shi, & Pajevic, ; Walsh & Choi, ). We investigated the possible interaction between activated T cells and miR‐21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OCs are key regulators of the bone modeling process, and several studies have shown that CD4 + T cells are closely related to the differentiation of OCs by secreting RANKL (Uda, Azab, Sun, Shi, & Pajevic, ; Walsh & Choi, ). We investigated the possible interaction between activated T cells and miR‐21.…”
Section: Resultsmentioning
confidence: 99%
“…Both in vivo and in vitro experiments further showed decreased RANKL expression in miR‐21 −/− mice, thereby inducing severe imbalance in the RANKL/OPG ratio, indicating that miR‐21 promoted tooth movement through RANKL/OPG. While RANKL is known to be synthesized by neutrophils, monocytes, dendritic cells, and especially osteoblasts and active T cells (Hu et al, ; Neve, Corrado, & Cantatore, ; Uda et al, ), how miR‐21 mediates RANKL expression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…; Uda et al . ). Part of the reason for this lies in the fact that the cartilage is not easily visualised; its thickness is inferred from the gap between the ends of the bone (the joint space) on a plain radiograph.…”
Section: Articular Cartilage Is Adapted To Withstand Mechanical Stressmentioning
confidence: 97%
“…It is now widely believed that osteocytes play key roles in the regulation of bone remodeling and in the mediation of bone mechanotransduction, although the mechanisms are currently incompletely defined. [1][2][3][4][5][6][7][8][9][10] Elucidating these mechanisms will advance the progress of bone biology research and help define new targets for the treatment of metabolic bone diseases.…”
Section: Introductionmentioning
confidence: 99%